2018
DOI: 10.5539/elt.v12n1p176
|View full text |Cite
|
Sign up to set email alerts
|

Revisiting the Writing Assessment Process at a Saudi English Language Institute: Problems and Solutions

Abstract: Over the past several decades, writing assessment has evolved in an ever-growing attempt to provide contextual fairness to a student while maintaining standards across a larger community. This study analyzed writing assessment at a Saudi English Language Institute (ELI) by first discussing teaching and learning in an EFL context before examining the shortcomings of current Saudi methods in assessment. A universal rubric created by the Saudi ELI allows for consistency across the program and cross-grading betwee… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
8
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(9 citation statements)
references
References 18 publications
1
8
0
Order By: Relevance
“…It is now possible to state that even though it was believed that allocating more grade weighting towards topic information development, maintenance, and organization, and coherence in assessing written academic discourse by Thai academic English writing teachers would be advantageous (Barkaoui, 2011;Connor & Farmer, 1990;Smit et al, 2017), the findings of this study do not indicate feasibility for such. According to the findings, the Thai academic English writing teachers were not able to significantly distinguish the progression of given to new topic information in written academic text, therefore, given to new information progression may not be a feasible source of writing quality assessment at this time (Alshakhi, 2018;Connor & Farmer, 1990;Todd, 2016).…”
Section: Discussionmentioning
confidence: 93%
See 2 more Smart Citations
“…It is now possible to state that even though it was believed that allocating more grade weighting towards topic information development, maintenance, and organization, and coherence in assessing written academic discourse by Thai academic English writing teachers would be advantageous (Barkaoui, 2011;Connor & Farmer, 1990;Smit et al, 2017), the findings of this study do not indicate feasibility for such. According to the findings, the Thai academic English writing teachers were not able to significantly distinguish the progression of given to new topic information in written academic text, therefore, given to new information progression may not be a feasible source of writing quality assessment at this time (Alshakhi, 2018;Connor & Farmer, 1990;Todd, 2016).…”
Section: Discussionmentioning
confidence: 93%
“…Traditionally, evaluating the writing ability of tertiary students has always been one of the more daunting tasks taken on by English as a foreign language (EFL) writing teachers. Research has shown that writing teachers dedicate countless hours examining, judging, and allocating more grade weighting toward the substantial aspects of an EFL students' academic writing, e.g., content, grammar, organization, punctuation, spelling, style, and vocabulary (Alshakhi, 2018;Beck et al, 2018;Cohen, 1994;Downing, 2015;Veloo et al, 2018). However, not all aspects in academic written discourse are equally important (Barkaoui, 2011).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Similarly, Aldukhayel (2017) explored the clarity and familiarity of three scoring rubrics that were used to assess students' writing achievement in the preparatory year program (PYP) in a Saudi university. Another study by Alshakhi (2019) aimed at exploring the weaknesses of the Saudi writing assessment methods employed at an English Language Institute. The results showed that replacing the existing holistic rubric with an analytic one can enhance contextual-based learning and eliminate cross-grading, to improve student-teacher relationship.…”
Section: Critical Analysismentioning
confidence: 99%
“…In addition to those issues, raters are often concerned about the scales of exemplary texts, how those scales are constructed, and what linguistics aspects should be included in them (Hamp-Lyons, 1990; Knoch, 2011;Alshakhi, 2019). In the Saudi context, writing assessment has hardly ever been a subject of agreement amongst practitioners, instructors, or even students for many years (Obeid, 2017;Alshakhi, 2018). Its complexity represents a challenge for many writing teachers.…”
Section: Introductionmentioning
confidence: 99%